Sexual functioning among young adult cancer patients: A 2‐year longitudinal study. Issue 2 (17th November 2017) - Acquati, Chiara; Zebrack, Brad J.; Faul, Anna C.; Embry, Leanne; Aguilar, Christine; Block, Rebecca; Hayes‐Lattin, Brandon; Freyer, David R.; Cole, Steve
Abstract : BACKGROUND: Cancer‐related sexual dysfunction has been reported among adolescents and young adults (AYAs); however, its prevalence over time has not been examined. This longitudinal study investigated sexual dysfunction in AYAs over the course of 2 years after the initial diagnosis. METHODS: Young adult patients (18‐39 years old) completed the Medical Outcomes Study Sexual Functioning Scale within the first 4 months of their diagnosis (n = 123) and again 6 (n = 107) and 24 months later (n = 95). An ordered multinomial response model analyzed changes in the probability of reporting sexual dysfunction over time and the independent effects of demographic, clinical, and psychosocial variables. RESULTS: More than half of the participants reported sexual functioning to be problematic at each assessment. The probability of reporting sexual dysfunction increased over time ( P < .01) and was greater for cancer patients who were female ( P < .001), older ( P < .01), married or in a committed relationship ( P < .001), treated with chemotherapy ( P < .05), and reporting comorbid psychological distress ( P < .001) and lower social support ( P < .05). For women, being in a relationship increased the likelihood of reporting sexual problems over time; for men, the likelihood of reporting sexual problems increased regardless of their relationship status. CONCLUSIONS: A substantial proportion of young adults report ongoing problems with sexual functioning in the first 2 years after their cancer diagnosis. These findings justify the need to evaluate and monitor sexual functioning throughout a continuum of care. Cancer 2018;124:398‐405 . © 2017 American Cancer Society . Abstract : More than half of young adults report problems with sexual functioning at each assessment, and increased probabilities of reporting sexual dysfunction can be observed over time and for cancer patients who are female, older, in a relationship, treated with chemotherapy, and reporting comorbid psychological distress and lower social support. For women, being in a relationship increases the likelihood of reporting sexual problems over time; for men, reporting sexual problems over time increases regardless of their relationship status.